In Memoriam Prof. Dr. İbrahim Mete Mısırlıoğlu - Tavuç, İbrahim (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2021)
Ibrahim Mete Mısırlıoğlu was a world renown earthworm taxonomist, and a valuable scientist both in Turkey and internationally. He passed away unexpectedly in 02. May 2021 at age of 49. He will be remembered as a leading soil zoologist in Turkey and the Middle East due to his out-standing contributions to oligochaete taxonomy, faunistics and biogeography and as a good person because of his charming personality and help-fulness.